511 Pathological sleep prolongation and sleep onset REM period. (3rd May 2021) - Honda, Makoto; Kimura, Shinya; Sasaki, Kaori; Wada, Masataka; Ito, Wakako
Abstract: Introduction: ICSD-3 employs two definitions of pathological sleepiness: sleep prolongation with 24-hour total sleep time (24hrPSG TST) ≥660 and high sleep propensity with mean sleep latency(mSL) ≤8 min on MSLT. Multiple SOREMPs on MSLT reflects the pathophysiology (sleep instability) of narcolepsy, but it is not clear whether the lack of SOREMPs is associated with the pathophysiology of idiopathic hypersomnia. We performed 24hr PSG and PSG-MSLT sequentially to understand the meaning of SOREMP in those with pathological sleep prolongation. Methods: Fifty-six consecutive patients visiting Seiwa Hospital or Koishikawa Tokyo Hospital affiliated to Institute of Neuropsychiatry with suspected idiopathic hypersomnia with habitually long sleep time were evaluated by 3-day sleep studies: unattended 24hr PSG followed by PSG and MSLT from January 2017 to November 2020. After excluding inadequate recordings or other sleep pathologies, we analyzed 52 data and found that 39 patients (23 females, 21.8 ± 7.9 years old, BMI 20.4 ± 2.5 kg/m2) exhibited pathological sleep prolongation. Results: We divided 39 patients with pathological sleep prolongation into those with at least one SOREMP(n=9) and those without SOREMP(n=30) and explored differences in clinical symptoms and PSG variables. There were no differences in conventional sleep variables except for PSG sleep latency, shorter in those with SOREMP (20.8min vs 43.8min, p=0.032). Also 24hr PSG sleep variables showed no differences except for the number of NREM-REM cycles, more in those with SOREMP (10.4 vs 8.1, p=0.037). Frequency of clinical symptoms such as REM related phenomena and various symptoms characteristic for idiopathic hypersomnia did not differ between groups except for less frequency of general malaise p=0.003 and orthostatic hypotension p=0.049 in those with SOREMP. We had similar results when we compared 5 patients with multiple SOREMPs and 30 patients without SOREMP. Conclusion: Our results indicated that sleep variables and clinical characteristics of idiopathic hypersomnia in those with pathological sleep prolongation were mostly the same regardless of the status of SOREMP on MSLT, suggesting that the absence of SOREMPs on MSLT were not fundamentally related to the pathophysiology of those with pathological sleep prolongation (idiopathic hypersomnia with long sleep time). Support (if any):